Galectin-3 and its relationship with the state of coronary arteries in patients with acute myocardial infarction and concomitant obesity - O. S. Yermak; P. H. Kravchun; N. H. Ryndina; H. Yu. Tytova; K. M. Borovyk (Zaporožskij Medicinskij Žurnal)
The aim of the study - to evaluate the condition of the coronary arteries according to quartile of galectin-3 serum level in patients with acute myocardial infarction and obesity.